(untitled) (REVISTA DE AGRICULTURA NEOTROPICAL, 2020)
The negative impact of livestock breeding on the environment has been mitigated through the combination of pastures and trees, characterizing the silvopastoral systems (SPS), an alternative to conventional pasture systems (CPS). The SPS provides environmental services, particularly the recovery of degraded areas and carbon sequestration. Furthermore, the complexity of the SPS can improve other environmental services, for example, enhance biodiversity and reduce pests through biological control. However, it is not clear the relationship between microclimate, pasture, trees, cattle, and invertebrate present in this environment. The purpose of this research was to characterize the macrofauna and determine the richness and abundance of invertebrates associated with dung patches of cattle raised in SPS and CPS pasture systems during two years in Brazil. As a result, we verified that the presence of trees in pastures alters the environment, notably through the reduction of solar radiation; decreases the wind speeds; attenuates the air and soil temperature, and diversifies the food supply, with the promotion of beneficial insect richness in dung patches of cattle. The diversity index of invertebrate fauna associated with dung patches in the SPS and CPS were respectively, 1.9 and 1.3. Besides that, the SPS contributed to higher densities of pupal parasitoids insects represented by Aphaereta sp. and Spalangia sp., the most important cattle ectoparasite controllers. In this way, we concluded that the integrated pasture systems are an essential tool for biodiversity improvement, especially the beneficial insects living in dung patches, which can contribute to reducing cattle ectoparasite infestations.